Boosting the Economic Recovery or Closing a Green Deal in Europe? Or Both? - Natacha Valla (Intereconomics, 2020)
The recovery measures announced by Europe in parallel with the Green Deal are the perfect opportunity to step up the effort to measure the impact of public expenditure, both in the short and in the long term. To that aim, it is essential to quickly stabilise benchmarks to measure the financial and non-financial impact of investments in the European recovery plan.
Keywords: 330; Coronavirus; Epidemie; Finanzpolitik; Stabilisierungspolitik; EU-Staaten